JWST ERS Program Q3D: The pitfalls of virial black hole mass constraints shown for a z ∼ 3 quasar with an ultramassive host - Bertemes, Caroline; Wylezalek, Dominika; Rupke, D. S. N.; Zakamska, N. L.; Veilleux, S.; Beckmann, Benjamin; Vayner, A.; Sankar, S.; Ishikawa, Y.; Diachenko, N.; Liu, W.; Chen, Y.-C.; et al. (Astronomy and astrophysics, 2025)
We present observations with the Mid-InfraRed Instrument (MIRI) and Near-InfraRed Spectrograph (NIRSpec) on board the James Webb Space Telescope (JWST), targeting the extremely red quasar J165202.64+172852.3 at z = 2.948 (dubbed J1652). As one of the most luminous quasars known to date, it drives powerful outflows and hosts a clumpy starburst, in the midst of several interacting companions. We estimated the black hole (BH) mass of the system based on the broad Hα and Hβ lines, as well as the broad Paβ emission in the infrared and Mg II in the ultraviolet. We recovered a very broad range of mass estimates, with individual constraints ranging between log MBH ∼ 9 and 10.2, which is extended further if we impose a uniform broad line region geometry at all wavelengths. The large spread may be caused by several factors: uncertainties on measurements (insufficient sensitivity to detect the broadest component of the faint Paschen β line, spectral blending, ambiguities in the broad or narrow component distinction, etc.), lack of virial equilibrium, and uncertainties on the luminosity-inferred size of the broad line region (BLR). The exotic nature of our target (luminous, starburst, powerful outflows, high accretion rate, and dusty centre) is another likely contribution to the large uncertainties. We broadly constrained the stellar mass of J1652 by fitting the spectral energy distribution, which suggests that the host is extremely massive, at ∼10 12.1 M⊙, with a 1.1 dex uncertainty at > 1 dex above the characteristic mass of the Schechter fit to the z = 3 stellar mass function. Notably, J1652’s central BH might be interpreted as being either over-massive or in line with the BH mass-stellar mass relation, depending on the choice of assumptions. The recovered Eddington ratio varies accordingly, but it exceeds 10% in any case. We set our results into context by providing an extensive overview and discussion of recent literature results and their associated assumptions. Our findings provide an important demonstration of the uncertainties inherent in the virial BH mass estimates of individual objects, which are of particular relevance in the JWST era, given the increasing number of studies on rapidly accreting quasars at high redshift.
Gesehen am 30.09.2025